2008
DOI: 10.1261/rna.1227808
|View full text |Cite
|
Sign up to set email alerts
|

The 3′ proximal translational enhancer of Turnip crinkle virus binds to 60S ribosomal subunits

Abstract: During cap-dependent translation of eukaryotic mRNAs, initiation factors interact with the 59 cap to attract ribosomes. When animal viruses translate in a cap-independent fashion, ribosomes assemble upstream of initiation codons at internal ribosome entry sites (IRES). In contrast, many plant viral genomes do not contain 59 ends with substantial IRES activity but instead have 39 translational enhancers that function by an unknown mechanism. A 393-nucleotide (nt) region that includes the entire 39 UTR of the Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
172
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(181 citation statements)
references
References 64 publications
6
172
2
1
Order By: Relevance
“…A tRNA-shaped 3Ј-CITE of TCV (TSS) was shown to bind directly to the 60S subunit and 80S ribosome, but not the 40S subunit, which leaves the question of how and where the 40S subunit is recruited (29). A TSS-like domain was also found in the 3Ј-UTR of pea enation mosaic virus RNA2 (62), adjacent to another 3Ј-CITE that binds eIF4E (63).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A tRNA-shaped 3Ј-CITE of TCV (TSS) was shown to bind directly to the 60S subunit and 80S ribosome, but not the 40S subunit, which leaves the question of how and where the 40S subunit is recruited (29). A TSS-like domain was also found in the 3Ј-UTR of pea enation mosaic virus RNA2 (62), adjacent to another 3Ј-CITE that binds eIF4E (63).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, plants contain a homolog of eIF4F termed eIF(iso)4F, consisting of eIF(iso)4E and eIF(iso)4G. The tRNA-shaped 3Ј-CITE of turnip crinkle virus binds directly to ribosomal 60S subunits and 80S ribosomes, but its interactions with initiation factors are unknown (29). The factor requirements of the most recently discovered 3Ј-CITE (from the Xinjiang isolate of Cucurbit aphid-borne yellows virus) are also unknown (30).…”
mentioning
confidence: 99%
“…18 In TCV, H4a loop sequences interact with upstream flanking sequences to form another pseudoknot (ψ3), which is functional in translation. 19 However, the formation of ψ3 is not important for non translated satC replication. In vivo genetic selection results revealed that satTCV H4a and H4b contain alternative structures in function to that of the wild type, which suggests that satC RNAs develop distinct elements to achieve similar functions.…”
mentioning
confidence: 99%
“…in Figs 3 and 4). The structural features that distinguish the two conformations of the ssRNA probe are not currently known, but it is probable that they are the result of the adoption of distinct higher-order structures similar to those described in the 3'-terminal region of other members of the Tombusviridae [McCormack et al, 2008;Na & White, 2006;Pogany et al, 2003;Wang & Wong, 2004] and also predicted in PFBV . Though RNA-binding properties have not been described so far for p27 homologues of other carmoviruses, the p27-binding capability parallels the results obtained with the equivalent replicase protein of TBSV, p33, the only related protein for which this question has been investigated [Rajendran & Nagy, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…Además de los elementos implicados en la replicación, se ha descrito la presencia de reguladores traduccionales en la 3´ UTR de distintos miembros de la familia Tombusviridae que parecen promover una traducción eficiente de los vRNA en ausencia de estructuras cap Stupina et al, 2008;Truniger et al, 2008;Wang et al, 2011b].…”
Section: Aspectos Generalesunclassified